Determining motivators and hygiene factors among excellent teachers in Malaysia: an experience of confirmatory factor analysis - Amzat, Ismail Hussein; Don, Yahya; Fauzee, Sofian Omar; Hussin, Fauzi; Raman, Arumugam (Emerald, 2017)
Purpose – In a world in which successful learning is believed to rest on the methods of teaching and the performance of students is determined by teacher quality, it is clear that teachers are the backbone of student learning attainments. In such a scenario, teacher development, welfare, motivation, and satisfaction are crucial for better teaching performance. Therefore, the purpose of this paper is to determine the motivator and hygiene factors among excellent teachers in Malaysia and to explore factors that lead to satisfaction and cause dissatisfaction among excellent teachers in Malaysia.